Construindo Conceitos de Ecotoxicologia no Ensino Básico: Experimentos com Plantas - Rodrigues, Victor Delamerlini; Cassimiro, Giovana Duarte; Ogura, Allan Pretti; Paro, Renata Martins dos Santos; Moreira, Raquel Aparecida (Ecotoxicology and Environmental Contamination, 2023)
Here we suggest a practical work in which toxicity tests are performed with plants to assess and scale effects on ecosystems. The seed germination test is used by Brazilian environmental agencies, such as the Environmental Company of the State of São Paulo (CETESB). The test is easy to handle, quick, and visually didactic, having the educational potential to build basic concepts of Ecotoxicology in primary education, such as species sensitivity, toxicity and dose-response. These activities are related to the student's daily life and the population in general and can be approached playfully, although it is still little applied in schools. Therefore, this work aimed to provide students from a basic and technological education school with an experience in scientific research through the evaluation of the germination of lettuce (Lactuca sativa), arugula (Eruca sativa), beans (Phaseolus vulgaris) and onion (Allium cepa) seeds when exposed to three home conventional products (bleach, detergent, and table salt) in different dilutions. The obtained results from the experiments carried out under conditions available in the school environment showed that the seeds used showed different sensitivities to varying concentrations of salt and bleach, with onion being the most sensitive plant species among those tested. As for the detergent, all seeds have similar sensitivities since this product was considered to have the most significant potential for toxicity among the tested species. Based on described experimental procedures, a practical class script for seed germination tests was proposed to contribute to the teaching-learning process in primary education to approach related concepts in the classroom regarding Ecotoxicology, bioindicators of environmental quality, and environmental contamination.